KAJIAN BENTUK KERIS JAWA TRADISIONAL DHAPUR KEBO DALAM ALAM PIKIRAN JAWA - Dony Satryo Wibowo (Jurnal Seni dan Reka Rancang: Jurnal Ilmiah Magister Desain, 2019)
AbstractThe design treasures of traditional Nusantara work, especially on the Javanese kris, deserve to beexamined for their uniqueness with in-depth discussion. Indonesian kris is recognized by UNESCOas a World Heritage Masterpiece. This international recognition cannot be underestimated. The worldrecognition of the excellence of Indonesian cultural work that has its roots in ancient times, suggest thatIndonesian people should be the host in their cultural studies. The spread of the Indonesian kris stemsfrom the creation of the initial form of the kris on the island of Java. One of the Javanese traditional kriswhich is unique and has special meaning is the keris with various forms of dhapur Kebo. The discussionof traditional designs of the dhapur Kebo variety of kris in the minds of Javanese people is explored witha qualitative approach and uses descriptive explanations to find socio-cultural facts that include thedesign of the dhapur Kebo in detail and depth. The kris with the dhapur Kebo is designed to end to bethin, with more accentuating its function as a sacred object than as a functional object. The kris withthe form of dhapur Kebo appears in the Javanese kris tradition as a class of sacred object dating back tothe Megalith era, to include the buffalo icon which is very useful for the fertility of agricultural fields indaily life in the heirloom of the ageman kris. The buffalo is specifically distilled in the traditional Javanesekeris design as a implied inscription, to be conveyed to future generations as well as an heirloom ofageman which is traditionalized in the convention standard of Javanese cultural thought.Keywords: keris, traditional design, buffalo, agrarian, Javanese culture. AbstrakKhazanah desain karya tradisional Nusantara, khususnya pada bilah keris Jawa, patutuntuk dikaji keunikannya dengan pembahasan yang mendalam. Keris Indonesia diakuioleh UNESCO sebagai Mahakarya Warisan Dunia. Pengakuan internasional tersebut tidakdapat dipandang sebelah mata. Ketika dunia mengakui keunggulan karya budaya Indonesiayang berakar sejak zaman purba, maka seyogyanya manusia Indonesia menjadi tuan rumahdalam kajian budayanya. Persebaran keris Indonesia bermula dari penciptaan bentuk awalkeris di pulau Jawa. Salah satu keris tradisional Jawa yang unik dan memiliki makna khususadalah keris dengan ragam bentuk dhapur Kebo. Pembahasan desain tradisional keris ragamdhapur Kebo dalam alam pikiran masyarakat Jawa, digali dengan pendekatan kualitatif danmenggunakan pemaparan deskriptif untuk mendapatkan temuan fakta-fakta sosial budayayang meliputi desain dhapur Kebo dengan terperinci dan mendalam. Keris dengan ragamdhapur Kebo didesain cenderung tipis, dengan lebih menonjolkan fungsinya sebagai bendasakral daripada sebagai benda fungsional. Keris dengan bentuk dhapur Kebo dimunculkandalam tradisi perkerisan Jawa sebagai golongan benda sakral yang dimulai sejak masaMegalitikum, untuk menyertakan ikon hewan kerbau yang sangat berjasa bagi kesuburansawah pertanian dalam kehidupan sehari-hari pada pusaka keris ageman. Hewan kerbausecara khusus distilasi dalam desain tradisional keris Jawa sebagai inskripsi yang tersirat,untuk disampaikan pada generasi penerus sekaligus sebagai pusaka ageman yang ditradisikandalam pakem konvensi alam pikiran budaya Jawa.Kata kunci: keris, desain tradisional, kerbau, agraris, budaya Jawa